The Impact of ESG Scores on Stock Returns : An Empirical Analysis of French Listed Companies - Ginepro, Benoît (2025)
This thesis investigates the relationship between Environmental, Social, and Governance (ESG) scores and stock returns among companies listed on the French stock market. Using data from Refinitiv Eikon and employing the Fama-French and Carhart multifactor models, the study analyses whether ESG performance, both in aggregate and by individual pillar (E, S, G), has a statistically significant impact on risk-adjusted returns over the 2017-2023 period. A High-Low portfolio strategy is used to compare the performance of firms with high versus low ESG ratings. The results reveal a negative relationship between overall ESG scores and stock returns, with companies exhibiting lower ESG ratings tending to outperform higher-rated peers, particularly in value-weighted portfolios. This suggests that companies with low ESG scores perform better than those with high ESG scores. When we examine the individual ESG components, the effects become more complex. Environmental and social scores have a neutral or statistically insignificant relationship with returns. In contrast, governance scores are strongly associated with overall ESG ratings. They also show negative abnormal returns and significant variability.